Understanding and Elevating Web Practice Through Web Analytics Final - Chawla, Swati; Singh, Dr. Gurdev (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Web analytics is the measurement, collection, analysis and summarizing of internet data for purposes of understanding and optimizing web usage. To check the web analytics the website IJCT is considered. This paper is the first step to analyze the availability and performability of the site. Availability depicts that for how much time the system is up i.e. check the utilization of the system on which that site works.Â Performability is the method to analyze each and every module separately and clearly in an efficient manner. Availability and performability collectively check the reliability of the system to ensure the performance measurement of that system. Web analytics is not just a tool for measuring and depicting website traffic but can be used as a tool for business research and market research, as well as a means to check and improve upon the effectiveness and utilization of a web site .The tool used for the web analytics for this site is AWStats. AWStats is an open source Web analytics reporting tool, which used for analyzing the amount of data from Internet services such as web, streaming media, mail and FTP servers .This tool check the performance of the IJCT separately by dividing one month module to days in month, week in month ,hours in month ,contributionÂ of various countries, traffic generated etc. This paper deal with the securitization of IJCT for January month to indicate how many events and functionality occurs during surfing on this journal by various users on the Web. This critique helps us to identify the throughput of IJCT. Â Here it is clear that users do not actually read: instead, they download and upload the data. A study of different online journals defines that this website scored massive response instead of the short time span. It completely and efficiently elaborate the usage of the IJCT by stating user visited, number of visits,Â number of hits ,bandwidth and many more.